2013
DOI: 10.3389/fphys.2013.00214
|View full text |Cite
|
Sign up to set email alerts
|

Social calls of flying big brown bats (Eptesicus fuscus)

Abstract: Vocalizations serving a variety of social functions have been reported in many bat species (Order Chiroptera). While echolocation by big brown bats (Eptesicus fuscus) has been the subject of extensive study, calls used by this species for communication have received comparatively little research attention. Here, we report on a rich repertoire of vocalizations produced by big brown bats in a large flight room equipped with synchronized high speed stereo video and audio recording equipment. Bats were studied ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…The recordings we made included search, approach and terminal phase calls (Griffin et al, 1960;Surlykke and Moss, 2000), which confirmed that the bats were foraging and not commuting from one site to another, corroborating a previous report of this area as a hunting field for E. fuscus (Surlykke and Moss, 2000). We did not record any calls that could be characterized as E. fuscus social calls (Gadziola et al, 2012;Wright et al, 2013Wright et al, , 2014. The AMSL of the echolocation calls recorded was 133-138 dB (RMS re.…”
Section: Discussionsupporting
confidence: 59%
“…The recordings we made included search, approach and terminal phase calls (Griffin et al, 1960;Surlykke and Moss, 2000), which confirmed that the bats were foraging and not commuting from one site to another, corroborating a previous report of this area as a hunting field for E. fuscus (Surlykke and Moss, 2000). We did not record any calls that could be characterized as E. fuscus social calls (Gadziola et al, 2012;Wright et al, 2013Wright et al, , 2014. The AMSL of the echolocation calls recorded was 133-138 dB (RMS re.…”
Section: Discussionsupporting
confidence: 59%
“…1). Using a combination of visual and auditory examination confirmed with results from a discriminant function analysis (DFA) to distinguish this call type from others [5], we identified FMB in 91 of the 322 two-bat recordings with at least one bat skilled at capturing the prey item and in none of the 603 single-bat recordings in this study. Table S3 summarizes the number of trials in each context and the number of trials of each type containing one or more FMB.…”
Section: Methodsmentioning
confidence: 56%
“…Synchronized high-speed video and audio recordings were acquired and digitally stored, allowing for careful analysis of call features and reconstruction of bat three-dimensional (3D) flight paths and positions. We examined bats’ behavior surrounding the frequency-modulated bout (FMB), a sequence of three to four calls, longer in duration and lower in frequency than typical big brown bat echolocation pulses [5; Fig. 1].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations